PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR IPA DITINJAU DARI MOTIVASI BELAJAR SISWA KELAS VIII SMP NEGERI 1 PRAMBANAN KLATEN TAHUN AJARAN 2013/2014 - Wahyuni Wahyuni; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
According to descriptive study, the research is intended to know the inclinationoftheresultofIPAlearninginclassVIIIgradeatSMP NEGERI 1Prambanan Klateninacademic2012/2013byusinginquirymodel,directinstruction,andthe learnmotivationofthestudent.Accordingtocomparativestudyistoknowthe differenceoftheresultofIPAlearningontheVIIIgradeatSMP NEGERI 1Prambanan Klatenstudentswiththelearnusinginquirymodel anddirectinstructionconsederation fromthelearnmotivationofthestudent. The research conducted at the eight grade of SMP NEGERIÂ  1 Prambanan Klaten. The research population included all students of the eight grade students of 7 classes. The removal of sample by random sampling. From the result lottery get class VIII C as experiment sample and class VIII D as control sample. The collecting data by using documentation techniques to obtain the first skill of the students, angket techniques to obtain the learn motivation and the test techniques to obtain learning outcomes of the students Validity of the questions were looked for by using product moment correlation. The question reliability was looked for using the KR-20 formula. The question reliability angket was looked for using the Alpha Cronbach formula. According to descriptive study, the result showed that the tendency of the result of IPA learning on SMP NEGERIÂ  1 Prambanan Klaten in 2012/2013 which using the model of learning inquiry in high categories with mean 23,18 on the interval 18,09- 23,26, and direct instruction models high categories with mean 21,07 on the interval 18,09-23,26. The tendency of the result of IPA learning on motivation which using the model of learning inquiry in high categories with mean 83,3 on the interval 76,6- 92,03, and direct instruction models high categories with mean 81,69 on the interval 76,68-92,03. In comparative there were significant difference of the result of ipa learning in using inquiry model n direct instruction consederation from the learn motivation of the student. From the result of anacova test before control motivation get value F 17,023 and after control motivation get value F 15,875 it means decrease 1,148 it means get removal the variable control is accurated. The teacher must be increase quality of learning outcomes beside using inquiry models to get maximal outcomes.Â